Lessons from community-led water sanitation and hygiene interventions in selected rural settlements of Oyo-State, Nigeria (2021)
Sustainability of Water, Sanitation, and Hygiene (WASH) interventions require a paradigm shift from the supply driven to community-led approach. Achieving this goal requires an understanding of local efforts and challenges faced in solving their WASH-related problems. This study addressed these concerns through a case study of two affected rural communities in Ibarapa East Local Government Area of Oyo State, Nigeria. Using eight focus group discussions with 92 male and female household heads, and key informants’ interviews with four community leaders, the study examined existing WASH situation and the community-led WASH interventions in the study area. Information garnered was audio-recorded, transcribed, and analysed using thematic analysis. Predominant ethnic group in the communities was Yoruba. Most were poorer than the average person. A distant stream, rainwater, and one uncompleted well were the water sources available in study locations and all had poor water quality. Open defecation was common due to the lack of modern toilets or latrines. Starvation, neighbourhood conflict, migration, skipping bathing and meals were major challenges related to WASH. Annual dredging of stream, repair of road linking the communities to the stream, enactment of laws prohibiting open defecating, and partnership with a rural development non-governmental organisation for support were major community-led WASH interventions in the study areas. Rural people tend to require external triggers or support to achieve sustainable solutions to hygiene problems. Collective community action triggered by a sense of disgust for inappropriate behaviours offers a more sustainable solution to WASH challenges.